2012
DOI: 10.1159/000336621
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Nephrectomy as a Rescue Therapy for Hemodialyzed Patient with Malignant Hypertension – Case Report

Abstract: We present the case of a 64-year-old male patient in whom malignant phase of hypertension developed during dialysis therapy. Hypertension was resistant to pharmacological therapy with seven antihypertensive drugs and dialysis therapy with ultrafiltration. In this patient bilateral nephrectomy was performed as a rescue therapy. It led to better control of blood pressure and allowed to reduce the number and dosage of antihypertensive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“… 1 We speculate that the disagreement among the other studies may be relevant to the distinct time of assessment. According to the report by Ferrario et al., the plasma Ang II of rats 48 hours after bilateral nephrectomy significantly dropped by 66%, 2 indicating that Ang II undergoes a prominent fall in plasma early after removal of renin from the kidneys.…”
Section: Discussionmentioning
confidence: 96%
“… 1 We speculate that the disagreement among the other studies may be relevant to the distinct time of assessment. According to the report by Ferrario et al., the plasma Ang II of rats 48 hours after bilateral nephrectomy significantly dropped by 66%, 2 indicating that Ang II undergoes a prominent fall in plasma early after removal of renin from the kidneys.…”
Section: Discussionmentioning
confidence: 96%
“…The kidney has been reported as a therapeutic target for RH, and bilateral nephrectomy was reported to achieve a good prognosis in preparation for renal transplantation in patients with malignant hypertension in 1980 (8). Since then, the usefulness of bilateral nephrectomy as a "forgotten treatment" for RH has been reported (7,(9)(10)(11). Renal denervation and nephrectomy have also been reported as effective treatment methods for RH targeting the kidney (12,13), but bilateral nephrectomy has been reported to be effective for RH with an inadequate response to renal denervation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that bilateral nephrectomy improves RH in dialysis patients (7)(8)(9)(10)(11). We performed bilateral nephrectomy and unilateral adrenalectomy to control blood pressure and the RAA system in a patient with RH complicated by hyperaldosteronism during hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Now it is practiced infrequently for refractory hypertension. The prevalence of bilateral nephrectomy as a treatment option ranges from 0 to 7 % in various countries [7] . Bilateral nephrectomy leads to reduction in the levels of renin, angiotensin and aldosterone, which subsequently lowers the blood pressure.…”
Section: Discussionmentioning
confidence: 99%